Antibody Response to COVID-19 mRNA Vaccine in Patients With Lung Cancer After Primary Immunization and Booster: Reactivity to the SARS-CoV-2 WT Virus and Omicron Variant. Issue 33 (20th November 2022) - Valanparambil, Rajesh M.; Carlisle, Jennifer; Linderman, Susanne L.; Akthar, Akil; Millett, Ralph Linwood; Lai, Lilin; Chang, Andres; McCook-Veal, Ashley A.; Switchenko, Jeffrey; Nasti, Tahseen H.; Saini, Manpreet; Wieland, Andreas; et al.
Abstract : PURPOSE: To examine COVID-19 mRNA vaccine–induced binding and neutralizing antibody responses in patients with non–small-cell lung cancer (NSCLC) to SARS-CoV-2 614D (wild type [WT]) strain and variants of concern after the primary 2-dose and booster vaccination. METHODS: Eighty-two patients with NSCLC and 53 healthy volunteers who received SARS-CoV-2 mRNA vaccines were included in the study. Blood was collected longitudinally, and SARS-CoV-2–specific binding and neutralizing antibody responses were evaluated by Meso Scale Discovery assay and live virus Focus Reduction Neutralization Assay, respectively. RESULTS: A majority of patients with NSCLC generated binding and neutralizing antibody titers comparable with the healthy vaccinees after mRNA vaccination, but a subset of patients with NSCLC (25%) made poor responses, resulting in overall lower (six- to seven-fold) titers compared with the healthy cohort ( P = < .0001). Although patients age > 70 years had lower immunoglobulin G titers ( P = < .01), patients receiving programmed death-1 monotherapy, chemotherapy, or a combination of both did not have a significant impact on the antibody response. Neutralizing antibody titers to the B.1.617.2 (Delta), B.1.351 (Beta), and in particular, B.1.1.529 (Omicron) variants were significantly lower ( P = < .0001) compared with the 614D (WT) strain. Booster vaccination led to a significant increase ( P = .0001) in the binding and neutralizing antibody titers to the WT and Omicron variant. However, 2-4 months after the booster, we observed a five- to seven-fold decrease in neutralizing titers to WT and Omicron viruses. CONCLUSION: A subset of patients with NSCLC responded poorly to the SARS-CoV-2 mRNA vaccination and had low neutralizing antibodies to the B.1.1.529 Omicron variant. Booster vaccination increased binding and neutralizing antibody titers to Omicron, but antibody titers declined after 3 months. These data highlight the concern for patients with cancer given the rapid spread of SARS-CoV-2 Omicron variant.